Standards-based reform and the poverty gap lessons for No Child Left Behind - Gamoran, Adam, 1957- (Brookings Institution Press, 2007)
"With latest data and research, scholars study what lessons can be drawn from earlier efforts to help NCLB achieve its goals. Authors show that standards-based reform has had some positive effects and some of the critics' greatest fears have not been realized. Recommendations offered for implementation of impending reauthorized NCLB"--Provided by publisher.